P PENERAPAN MOTIF FLORA KAYONAN BALI PADA MEJA DAN KURSI BELAJAR - Kadek Angga Putra; I Nyoman Dana; I Gusti Ngurah Agung Jaya CK (Hastagina : Jurnal Kriya Seni, 2021)
The work entitled "The Kayonan Bali Motif On The Tables And Chairs" was a form of the creator's response to the pandemic situation that resulted in learning done from home. In this creation, the focus of the work will be embodied in tables and learning. The application of the Balinese motive of the kayonan flora on the tables and chairs was intended in addition to giving a new visual so that the work would have Balinese cultural art value, for in a Balinese kayonan is the art of fine arts, the art of the display value of Balinese culture. The design stage begins with the collection of data as reference in the design of tables and chairs of learning.The technique used in the creation of these tables and learning chairs was that the cast used the polyester resin 3126. In the process, the  material is cast using a safe aga paint because it has been through the elimination process. Then the parts already cast are assembled based on the work image and last on finishing using mowilex 504. Table called darana's calm sense and chair called an prejudicial to focus is expected to be useful for learning on time pandemic. These tables and learning chairs are also expected to provide a sense of pride for users, especially for the younger generation, to love and preserve the Balinese cultural arts even more.